FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TIMBULNYA PLAK GIGI PADA ANAK SEKOLAH DASAR NEGERI 130 PALEMBANG - RA ZAINUR (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2015)
Brushing your teeth has become a part of life. Brushing has been taught for generations to every generation. Now toothbrush is a need both to children and parents. Generally, people brushing their teeth to clean the tooth surface of the leftovers. Brushing teeth regularly is not guarantee of free oral health problems, such as plaque which later evolved into dental caries and corals as well as other dental diseases. But at least been able to reduce plaque itself so minimize the growth of bacteria that can cause gum disease (Anonymous. 2012). Lack of public understanding about the selection of children's toothbrushes akan mempengaruhi Plaque scores of the child. Researchers will conduct research on student Ii in the Elementary School 130 Palembang is because previous students Ii in the Elementary School 130 Palembang've never done oral health examination to be used as a comprehensive clinic patients as well as student Ii Elementary School 130 Palembang. Based on the above, the writer is interested to discuss about Factors Associated With Incidence of Dental Plaque in Children Elementary School (SD) State 130 Palembang Year 2014 Population is the subject of research. In this study population, the entire student Ii Elementary School Palembang in 2014 amounted to 130 181 people. A sample is a subject of research. In this study sample, the majority of students Ii Elementary School 130 of Palembang in 2014 totaled 47 orang.Hasil study showed no correlation between the physical anatomy of the teeth, scraping the food, the type used toothbrush, tooth brushing techniques and types of food simultaneously with dental plaque in children in elementary school of 130 Palembang Year 2014 at the end of the study are suggested in an effort to prevent the occurrence of dental plakue the students need to do counseling and practice correct brushing techniques to students in order to improve oral health.